Implementasi Kegiatan Outing Class Dalam Menstimulasi Kemampuan Bahasa Ekspresif Anak Usia 5-6 Tahun Di TK Islam Thoriqul Jannah Kabupaten Sinjai - zahra Nurdin Umar; Azizah Amal; Fadhilah Afifah (Jurnal Kajian Anak (J-Sanak), 2026)
Learning activities that are often carried out in the classroom and are centered on teachers sometimes limit children's opportunities to interact and express themselves. Therefore, outing class activities are considered to be able to provide good stimulation to children's expressive language skills. The purpose of this study was to determine and understand the implementation of outing class activities in stimulating expressive language skills in children aged 5-6 years. This study uses a qualitative approach with a descriptive type. The sources in this study were the Principal and 1 Group B Teacher and 26 children aged 5-6 years who became the subjects of observation of expressive language skills. The location of the study was carried out at Thoriqul Jannah Islamic Kindergarten. Data collection was carried out through structured in-depth interviews with the principal and 1 group B teacher, documentation, and relevant archival materials. Children were observed directly using observation sheet guidelines. The data analysis process includes data reduction, data presentation, and formulation of conclusions. The research findings show that the implementation of outing class activities at Thoriqul Jannah Islamic Kindergarten, Sinjai Regency, has been carried out effectively and systematically, covering three stages: (1) Planning, which includes aligning the vision and mission of the nature school, preparing a Learning Implementation Plan (RPP) in accordance with STPPA, selecting topics/subtopics, identifying nature school-based locations, and arranging activity schedules; (2) Implementation, which is realized through various nature exploration activities such as visits to the school garden (cleaning flower pots), rice field areas (observing buffaloes), the area behind the school (collecting soil), and the hut in the school yard (planting cacti); and (3) Evaluation, which is carried out through daily assessments based on observations of children's learning outcomes and semester evaluations in the form of progress reports (report cards). Outing class activities provide good stimulation to the expressive language skills of children aged 5-6 years. The majority of children reach the Very Well Developed (BSB) category in three main indicators: the ability to express ideas or opinions, vocabulary, and the ability to retell experiences gained.